A sustainable business profit through customers and its impacts on three key business domains: technology, innovation, and service (TIS) - Lulaj, Enkeleda (Business, Management and Economics Engineering, 2023)
Purpose – This research examines and investigates the importance of sustainable business profit through customers and its impacts on three key business domains: technology-innovation-service (TIS). The main goal was to see what were the interrelationships of business-consumers and consumers-business analysis to have a sustainable profit based on the models: Innovation and Growth Teams (IGT), Innovative Customer Relationship Management (ICRM), Business-to-Consumer (B2C), Customer Service and Support (CSS), Customer Service Technology (CST), and Multidimensional Scaling model (MDS) or the factors (F1–F14). Were these factors important to businesses and which variables had the greatest impact on sustainable profit through consumer evaluation during purchase? Research methodology – This research was carried out on manufacturing, service, and distribution businesses (consumer-business analysis) and consumers (business-consumer analysis) in 200 businesses and consumers, through the completion of the online questionnaire and the meeting with the business managers, considering the same variables during the period (2019–2022). The data processing was done through (SPSS Statistics 23) using tests and econometric analysis (descriptive, factorial, reliability, multiple regression, and multidimensional scaling analysis) the model shows that all factors have great effects on sustainable business profit through consumers. Findings – However, it is suggested that of great importance for a sustainable business profit through customers are: the behavior of workers and staff, handling requests faster, business support before and after purchase, providing information applications (discount, usage, term of the expiration date, product content, payment methods as well as the provision of transport by the business for consumers. Research limitations – The limitations of this research are only a certain number of variables, years, and the number of businesses, but for other analyses and research, researchers can take a larger number of variables, businesses, and/or countries using the same models. Practical implications – Based on the above questions, it was confirmed that a (TIS) through models will make the profit even more stable by strengthening the position of businesses in the market against their competitors. So, in this case there are still practical implications in three key business domains (TIS) technology, innovation, and services. Therefore, businesses should pay attention to these findings to have a sustainable business profit. Originality/Value – Research related to sustainable profit through consumers considering three key business domains technology, innovations, and services (TIS) has not been analyzed earlier in terms of consumers as buyers and businesses as providers of products and services.